Provocative mathematics questions: drawing attention to a lack of attention - Klymchuk, S (Oxford University Press, 2015)
The article investigates the role of attention in the reflective thinking of school mathematics teachers. It analyses teachers’ ability to pay attention to detail and use their mathematical knowledge. The vast majority of teachers can be expected to have an excellent knowledge of mathematical techniques. The question examined here is whether this kind of knowledge might structure their attention in such a way that the emphasis on procedures deflects their attention from the essential details. Four groups of participant teachers from New Zealand, Hong Kong, Germany and Ukraine were given a mini-test containing seven simple mathematics questions. Most questions in the test were provocative in the sense that they looked like routine questions but in fact had some catch. The results of the test were startlingçthe vast majority of the participants gave incorrect answers to most questions in the test. After the test, the participants were given a short questionnaire to reflect on their performance on the test. Their responses were analysed using the theories of selective, divided and focused attention and Mason’s concept of the discipline of noticing. Implementations of the results of the study in assessment and professional development are discussed.
Keywords: Attention; Assessment; Knowledge; Professional development